WristOrigami: Exploring Foldable Design for Multi-Display Smartwatch - Zhu, Kening; Fjeld, Morten; Unluer, Ayca (ASSOC COMPUTING MACHINERY, 2018)
We present WristOrigami, an origami-inspired design concept and system extending the interaction with smartwatches through a foldable structure with multiple on-wrist displays. The current design provides extra affordances via folding, flipping, and elastic pulling actions on a multi-display smartwatch. To motivate the design of WristOrigami, we developed a taxonomy that could be useful for analyzing and characterizing the origami-inspired multi-display smartwatch interaction. Through a participatory-design study with a set of prototypes with different levels of fidelity, we investigated users' perception of WristOrigami in a wide range of applications with the presented features, and summarized a list of common shape configurations. We summarized our findings into seven design recommendations, to inform the future design of foldable smartwatch interactions. We further developed a set of application demonstrations as proofs-of-concept.
Keywords: Smartwatch; Foldable; Shape-changing Interface; Organic User Interface; Computer Science; Engineering